IMPLEMENTATION OF COMPLEMENTARY MIDWIFERY SERVICES ON MOTHER - Kusmindarti, Indah; Prameswari, Veryudha Eka (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Background: Complementary therapy is one of the community’s treatment options, especially for pregnant and giving birth women. In various health service settings, quite a few clients ask health workers, such as midwives, about complementary or alternative therapies. This happens because clients want to get services according to their choices, so if their wishes are fulfilled, it will have an impact on client satisfaction. This can be an opportunity for midwives to play a role in providing complementary therapy. Regarding complementary therapy, it is regulated in the Decree of the Minister of Health No. 1109/Menkes/Per/IX/2007 concerning complementary-alternative medicine. Objective: to determine the implementation of complementary midwifery services at the Independent Midwife Practice Place (TPMB) in the Blimbing area, Kesamben District, Jombang. Method: Survey, descriptive type with quantitative and qualitative approaches. The population in this study were all midwives who carry out midwifery practice independently and provide complementary therapy in the Blimbing area, Kesamben subdistrict, Jombang, a total of 5 midwives. The total sample taken was 5 TPMB. The data was analyzed and presented quantitatively in the form of a frequency distribution and qualitatively using an interactive model according to Miles and Huberman in Sugiyono (2013). Results: complementary midwifery services were provided by 5 respondents. Respondents were 30-49 years old, had midwifery education at Diploma III Midwifery and Midwifery Professional level, and had been in independent practice for more than 8 years. The types of services provided are 2-5 types, namely acupressure, baby/toddler massage, oxytocin massase, use of herbal medicine/traditional as a complement to conventional medicine, and yoga.